Analysis of the Practical Use of Geoinformation Systems for Territorial Management and Determination of Their Critical Properties - Chabaniuk, V.S.; Kolimasov, I.M. (Cybernetics and computer engineering, 2020)
The purpose of the paper is to analyze the use of GIS developed by the authors for the management of large territories and to determine their main critical properties. Critical GIS properties are being sought to manage territories that: 1) repeat for all such GIS, 2) differentiate them from conventional GIS, 3) must be taken into account when creating new GIS. Метою роботи є аналіз використання розроблених авторами ГІС для керування великими територіями та визначення їх основних критичних властивостей. Відшукуються критичні властивості ГІС для керування територіями, які: 1) повторюються для всіх таких ГІС, 2) відрізняють їх від звичайних ГІС, 3) повинні обов’язково враховуватися під час створення нових ГІС. Цель статьи — анализ использования разработанных авторами ГИС для управления бо льшими территориями и определение их основных критических свойств. Отыскиваются критические свойства ГИС для управления территориями, которые: 1) повторяются для всех таких ГИС, 2) отличают их от обычных ГИС, 3) должны обязательно учитываться при создании новых ГИС.